Modern Trends in Further Professional Education of Judges: Russian and Foreign Experience - Elena V. Burdina; Sergey V. Alexandrov (National Research Mordova State University, 2022)
Introduction. Modern further professional judicial education has a direct impact on the institutional and personal parameters of judicial independence and has a public significance as a guarantee of a judge's competence during his long career. The relevance of the research consists in development and substantiation of theoretical and methodological foundations of further professional education of judges as an independent form of their continuing education. The aim of the article is to systematize Russian and foreign experience in the organization of judicial professional development, to fill in the need for a comprehensive solution of legal, organizational and educational issues of judicial re-training, to substantiate promising models of the educational process and educational practices of continuous training of judges. Materials and Methods. The object of the study was further professional education of judges as a state-legal and educational institute. The comparative nature of the research, based on the study of modern domestic and foreign experience in organizing further education for judges, provided data that had not previously been analyzed in the Russian scholarly literature. On the basis of a comprehensive (interdisciplinary) approach, conclusions were obtained concerning both the issues of legal regulation of the procedure of further professional education of judges and issues of pedagogical nature. A systematic analysis of further professional education of judges predetermined the identification of specific features of teacher training, the nature of training programs, methods and technologies of training of judges. Sociological methods were used to formulate conclusions on the conditions of admissibility of the electronic educational process in the judicial classroom. The research drew on electronic resources that reveal organizational peculiarities and educational practices of national and foreign judicial schools. Results. Regularities determining the trends in the evolution of further professional education of judges in Russia and abroad have been determined and disclosed. Models of judicial schools operating in foreign states depending on their legal status, nature and types of educational processes were identified. The principles of organization of further professional education of judges, allowing to distinguish this type of education from traditional systems of higher legal education, were substantiated. Proposals for improving the legal and educational model of the Russian judicial school are formulated. Discussion and Conclusion. The results of the study can be useful for the further development of the theory of specialized judicial education, the definition of the legal status of the Russian judicial school that performs the functions of continuing education of judges, as well as for improving the educational process, given the need for methodological diversity of further programs and methods of training of judges.